120k views
2 votes
I Do not understand this problem what so ever pleasse help

I Do not understand this problem what so ever pleasse help-example-1

1 Answer

6 votes
The best way to solve this problem is to graph it, as shown below. The y-intercept is 3 and the graph is increasing.

If you wanted do this without a graph, you would substitute 0 for x in the equation to find y (the y-intercept is found when x=0).
y=3(2)^0
y=3(1)
y=3

Then we could test different value of x to see if the graph increases or decreases.

y=3(2)^0=3
y=3(2)^1=6
y=3(2)^2=27

We see that the values of y are increasing as the values of x are increasing, therefore, the whole graph is increasing.

:)
I Do not understand this problem what so ever pleasse help-example-1
User Eladian
by
5.9k points